EFFICIENCY OF WIRELESS CHARGING SYSTEMS IN HIGH-SPEED ELECTRIC VEHICLES - Taryana Taryana; Chak Sothy; Ardi Azhar Nampira (Journal of Moeslim Research Technik, 2025)
The increasing adoption of electric vehicles (EVs) necessitates the development of efficient charging solutions. Wireless power transfer (WPT) technology has emerged as a promising method for enhancing the convenience and efficiency of EV charging. Understanding the efficiency of WPT systems in high-speed charging applications is critical for their widespread implementation. This research aims to evaluate the efficiency of wireless charging systems for high-speed electric vehicles. The study investigates various factors affecting energy transfer efficiency, including alignment, distance, and frequency of operation. An experimental setup was created to test a wireless charging system under controlled conditions. Efficiency measurements were taken at different distances and alignments between the transmitter and receiver coils. Data were analyzed to identify optimal operating conditions and performance metrics. The findings indicated that the wireless charging system achieved an overall efficiency of 85% under ideal conditions. Efficiency decreased with increased distance between the coils, with a notable drop at distances exceeding 20 cm. Optimal alignment was found to enhance energy transfer, significantly improving overall system performance. The study demonstrates that wireless charging systems can be efficient for high-speed electric vehicles, with potential for practical applications in urban environments. These findings highlight the importance of optimizing system design and alignment to maximize efficiency.